Identifikasi dan Manajemen Risiko Untuk Mereduksi Kerentanan Pada PT. Bank Negara Indonesia (Persero) Tbk - Fajari Illahiah, Dian; Helmi, Sulaiman (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
Errors in analysis and management are vulnerable to making the implementation of regulations set by the government, agencies, and non-governmental organizations be carried out as desired. Like, prone to become one of the crucial domains to build a nation and reach the targets of an agency. This study has the intention of providing an explanation related to the definition, purpose and use of analysis, and risk management interventions so that PT. BNI (Persero), Tbk. The assessment category is a survey through a quantitative approach. The samples in the study were workers and managers of PT BNI (Persero), Tbk. This study uses core data and secondly, through the analytical method used is a descriptive qualitative method, and uses data analysis with decision analysis, on ERM matters. Obtaining the Koran provides Risk Management carried out by PT BNI (Persero), Tbk in accordance with BI regulations, this problem appears in the orderliness and discipline of the Company's Risk Management Division function to minimize vulnerability at PT.BNI (Persero), Tbk.